Budżet gmin Brody i Gubin na tle polskich gmin związanych z wydobyciem węgla brunatnego = Brody and Gubin municipalities budget against polish municipalities connected with lignite mining - Greinert, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Local Government Act requires the local level a number of obligations, which requires the expenditure for these purposes the relevant sum. Municipalities cover their expenses from various sources, increasingly looking for extra-budgetary funds. For this purpose, among others, located in the hands of the community estate, especially land.
Keywords: budżet gminny; wydobycie węgla brunatnego; korzyści z industrializacji; municipal budget; lignite mining; benefits of industrialization